Clinical requirements for extracellular vesicle assays. Issue 1 (1st December 2019) - Ayers, Lisa; Pink, Ryan; Carter, David Raul Francisco; Nieuwland, Rienk
ABSTRACT: The scientific and clinical interest in extracellular vesicles (EV) has grown exponentially during the past 15 years. As most research indicates that EVs can be utilised in diagnostics, prognostics and therapeutics, we may be on the brink of establishing the clinical utility of EV measurement, but how can we make this a reality? If we are to introduce EVs as biomarkers into clinical laboratories, it will be necessary to offer fully validated, International Organization for Standardization (ISO) standard 15189 assays. ISO 15189 defines the quality management system requirements particular to medical laboratories and is used internationally to determine accreditation. In order for a clinical laboratory to offer an accredited test for EVs, this assay must have been subjected to a thorough assay validation process. This process requires the generation of data related to defined performance characteristics, to ensure that an assay is performing in accordance with the needs of its clinical users. Each of the defined performance characteristics will be discussed in this review, along with the issues that specifically affect EV analysis. Accreditation is increasingly important for all clinical laboratories and the standards required to achieve this are becoming more and more stringent. Therefore, as companies seek to develop the best assays to detect EVs and their molecular contents for clinical utility, and as we move rapidly towards our goal of offering EV analysis in the diagnosis and monitoring of disease, it is timely to highlight the requirements for the clinical accreditation of such assays. It is essential to consider these parameters to ensure that we develop the highest quality assays possible and ultimately the best outcomes for patients.